(untitled) - Twomey, Rosemarie Feuerbach (Boston, 2010)
Employment Law: Going Beyond Compliance to Engagement and Empowerment, by Rosemarie Feuerbach Twomey, focuses on the laws that have the greatest impact on the relationships between employers and employees—in particular, the common law governing the employment relationship which has dramatically changed the application of the employment at will doctrine, and the many statutory requirements of fair employment practices that promote equal opportunity to all employees.
Keywords: Labor laws and legislation,Luật Lao động và pháp luật; United States,Hoa Kỳ